2014
DOI: 10.1108/ijse-12-2012-0240
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and deprivation of immigrants vs. natives in Italy

Abstract: Purpose – Italy has become a migrant receiving country and it has to face with the problem of social inclusion of immigrants. The purpose of this paper is to measure the gap on poverty and deprivation between immigrants and natives since manifest conditions of both of them are an important signal, although not exclusively, of social exclusion. Design/methodology/approach – Poverty analysis typically relies on a single monetary variable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Finally, a long theoretical and empirical tradition having its roots in the Chicago School research (Park 1950) and then taken up by supporters of the ''assimilationist model'', identifies the duration of stay as a key factor in bridging the gap between immigrants and natives. The paper of Berti et al (2014) based on the same dataset as the one that is used in this analysis supports the above-mentioned hypothesis with reference to the risk of poverty. They found that the length of stay seems to produce beneficial effects in terms of the risk of poverty even if for almost all of the deprivation indices considered in the multidimensional analysis of poverty, the gap between immigrants and natives does not decrease with time.…”
Section: Determinants Of the Within Inequalitymentioning
confidence: 81%
See 1 more Smart Citation
“…Finally, a long theoretical and empirical tradition having its roots in the Chicago School research (Park 1950) and then taken up by supporters of the ''assimilationist model'', identifies the duration of stay as a key factor in bridging the gap between immigrants and natives. The paper of Berti et al (2014) based on the same dataset as the one that is used in this analysis supports the above-mentioned hypothesis with reference to the risk of poverty. They found that the length of stay seems to produce beneficial effects in terms of the risk of poverty even if for almost all of the deprivation indices considered in the multidimensional analysis of poverty, the gap between immigrants and natives does not decrease with time.…”
Section: Determinants Of the Within Inequalitymentioning
confidence: 81%
“…Within a household where at least one member is a foreigner, a further classification is made between (1) households composed of individuals with the citizenship of a more developed country 5 (MDC), possibly living together with some natives; (2) households composed of all members with the citizenship of a country with Strong Migration Pressures (SMP) and (3) households that include both natives and foreigners from countries with SMP (mixed households). The second of the above groups can be described as immigrant households, according to a definition that has been already used for the Italian case in previous studies (Berti et al 2014).…”
Section: Data and Definitionsmentioning
confidence: 99%
“…The computation of the deprivation indicators of the IFR approach involves a long process as reported also in Berti et al (2014) and Betti et al (2015). In details, the IFR method follows seven main steps: (1) identification of the relevant survey items; (2) transformation of the items into the [0,1] interval, (3) exploratory and/or confirmatory factor analysis to define the latent dimensions; (4) computation of the weights 8 within each dimension; (5) calculation of the scores for each dimension; (6) calculation of an overall score and the a parameter as for the FM measure; (7) calculation of the deprivation indices.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the proportion of families living below the national (relative) poverty line among the families entirely composed of foreigners is 34.5% in 2017 (23.9% among mixed families) vs. 10.5% among Italian families (Istat 2018). Moreover, migrants are the poorest among the poor and a large number of studies in various contexts, confirm that poverty among migrants tends to be more marked and persistent than among natives in various countries (Bárcena-Martìn and Pérez-Moreno 2016; Kazemipur and Halli 2001;Lelkes 2007; de Bustillo and Anton 2011; Obućina 2014; Pastor 2014) and in Italy as well (Berti et al 2014). Various explanations have been attempted, to better account for the link between migration and poverty.…”
Section: Background Research On Migrants' Povertymentioning
confidence: 99%
“…improvement of global health and wellbeing). Additionally, as many scholars acknowledge, poverty among migrants is generally more acute and persistent than among the host population (Bárcena-Martìn and Pérez-Moreno 2016; Berti et al 2014;Kazemipur and Halli 2001;Lelkes 2007; de Bustillo and Anton 2011; Obućina 2014; Pastor 2014) and so reducing migrants' poverty is a key step to reduce the overall level of poverty in the whole society, particularly in countries with large immigration flows, like Italy. This motivates the focus of the present paper, which is specifically devoted to the ranking of migrants' families, for policy targeting.…”
Section: Introductionmentioning
confidence: 99%